Formation of Behavioural Finance as the Natural Stage of the Human Model Evolution in Economics - Ivanitsky, Viktor Pavlovich; Aleksandrov, Sergey Aleksandrovich (Economy of Regions, 2017)
The paper presents the background analysis of the formation of human model in economics. in the conditions of the constantly performing development of the economic science until the neoclassic paradigm and its modifications. Among them is behavioural finance, which presents a special interest for modern researchers. The evolution of the model of making economically significant decisions in inter-temporal and essential dimensions is the subject matter of the research. We have shown that the concept of the economic human model itself is the multidimensional one. In parallel with the processes of economical, social and political changes and economic science development, the economic human model was becoming more complex and relevant for each period of time. In this regard, we followed the stages of defining the concept of “subject rationality”. The study determines the significant traits implemented by researchers to create a full and consistent human model. We demonstrate the gradual development of economists’ idea of different types of the motivation of economic agents. Along with the financial factors of motivation, the scientists begin to take into account non-financial ones. This approach can help researchers get more “humanistic” view at the economic human. The modern concept of the economic human with attention to its implicit restrictions is formed through the complication of requirements to the rationality and its components crystallization. In the paper, we characterize contribution of the domestic scientists to the development of new directions of economic theory. The research describes the role of different regional economic scientific schools in the process of the formation of the Russian behavioural finance school.